Economic diversification as a strategic developmental alternative within the framework of sustainable development - Salah Mahrez; Tarek Rachi (Social Empowerment Journal, 2019)
The objective of this paper is to analyze the economic diversification strategy as a sustainable development alternative in the Arab oil countries and to demonstrate the benefits of economic diversification in practice to achieve significant progress in building a diversified economy in various sectors including tourism, real estate, banking, aviation, clean energy, At present, these sectors are generating significant proportions in national output.